2016
DOI: 10.1021/acs.chemmater.5b04521
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Control by Quantum Confinement and Surface Ligand Coating of Photocatalytic Efficiency in Chalcopyrite Copper Indium Diselenide Nanocrystals

Abstract: ABSTRACT:In the past few years, there has been an immense interest in the preparation of sustainable photocatalysts composed of semiconductor nanocrystals (NCs) as one of their component. We report here, for the first time, the effects of structural parameters of copper indium diselenide (CuInSe 2 ) NCs on visible light driven photocatalytic degradation of pollutants under homogeneous conditions. Ligand exchange reactions were performed replacing insulating, oleylamine capping with poly(ethylene glycol) thiols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 96 publications
1
24
0
Order By: Relevance
“…In the Randles circuit diagram, R s describes the resistance of the solution with regards to the movement of electrons, R ct is the resistance charge transfer occurring at the surface of the modified GCE\G1PPT‐CuInSe 2 QD. CPE is considered to be the constant phase element (double layer capacitance) occurs when there is a fluctuation of current because of the adsorption of ions the electrode surface and W s is the Warburg impedance component arising from ion diffusion quotients [81]. The kinetic parameters obtained from fitting the EIS fitting of the G1PPT‐CuInSe 2 QD are shown in Table S‐1 ( ESM) .…”
Section: Resultsmentioning
confidence: 99%
“…In the Randles circuit diagram, R s describes the resistance of the solution with regards to the movement of electrons, R ct is the resistance charge transfer occurring at the surface of the modified GCE\G1PPT‐CuInSe 2 QD. CPE is considered to be the constant phase element (double layer capacitance) occurs when there is a fluctuation of current because of the adsorption of ions the electrode surface and W s is the Warburg impedance component arising from ion diffusion quotients [81]. The kinetic parameters obtained from fitting the EIS fitting of the G1PPT‐CuInSe 2 QD are shown in Table S‐1 ( ESM) .…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic voltammetry measurements indicated that the valence band edge ( E VB ) of Cu x In y S QDs (Cu/In=1:6) is about 1.05 V (Figure S8, vs. normal hydrogen electrode, NHE). In combination with the band‐gap data obtained from the absorption spectra, the conduction band edge ( E CB ) of Cu x In y S QDs (Cu/In=1:6) is approximately −1.15 V. This makes electron transfer from QDs to Ni 2+ /Ni 0 (−0.25 V vs. NHE) or Ni 2+ –GSH (−0.95 V vs. NHE, see below) thermodynamically possible.…”
Section: Methodsmentioning
confidence: 99%
“…Surface ligands are generally introduced during the colloidal synthesis of nanocrystals; however, most of the ligands, long-chain aliphatic amines and phosphines (neutral 2-electron donating L-type) , and long-chain aliphatic carboxylates and phosphonates (1-electron donating X-type), , are insulating in nature. Therefore, in order to enhance the electrochemical and charge transport properties, , and biological imaging detection of nanocrystals, postsynthetic surface ligand exchange is routinely carried out. The ligand exchange reaction strongly affects the emission properties (PLQY and PL lifetime) ,, and excitonic absorption characteristics of nanocrystals. , Recently Weiss and co-workers, , our group, , and others have shown that postsynthetic ligand exchange of CdSe and/or CdS nanocrystals with X-type ligands induces the delocalization of quantum-confined holes causing a red-shift in the first excitonic absorption peak, which can be characterized as an “increase the confinement box size”. , However, such change in the optical properties was found to be irreversible.…”
Section: Introductionmentioning
confidence: 99%